SENSITIVITY OF MICROORGANISMS TO ETIOTROPIC MEDICINES AFTER MICROAEROPHILIC CULTIVATION’S CONDITIONS - Sklyar, N.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The effect of microaerophilic conditions of cultivation on sensitivity of microorganisms to etiotropic medicines has been studied. It was shown that antibiotic resistance of bacteria and yeast-like fungi of Candida genus increased after effect of above-mentioned factor. It was found that yield sensitivity changed to moderate one for (40,0±20,0) % of Staphylococci in relation to erytromycinе, laevomycetinе, lincomycinе, furazolidonе; for (20,0±10,0) % of Escherichia coli in relation to tetracyclinе; for 100 % of yield-like fungi of Candida genus in relation to itraconazole, fluconazole, ketоconazole. Appearance of resistance has been defined for (15,0±5,0) % of Staphylococcus spp. strains in relation to furazolidonе and laevomycetinе; for (30,0±10,0) % of Candida strains in relation to amphotericin. Antibiotic sensitivity of selected objects to cefalosporins of different generations was shown to be unchanged. It was found that lysis activity of specific bacteriophages in relation to staphylococci and escherichia coli was 4-32-fold increased.